Moral Rebellion and Religiusity in Pious Muslim Novels: Chavchay Saifullah and Muhidin M Dahlan Review of Sociology of Literature - Herdi Sahrasad; Muhammad Ridwan (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
This article argues that novelists Muhidin M Dahlan and Chapchay Syaifullah tried to make moral and religious rebellions in their work as a result of existing social conditions. They rebel against normative and established values, old order and social arrangements. They are creative in the context of literature as a fictional world built with the spirit of renewal and enlightenment. And here, imagination is a significant creative process for deconstruction and enlightenment as well as upheaval in religiosity, religious rebelion, religious dissent.In this context, Muhidin and Syaifullah novels do not place religious life as a problem solver. Borrowing Goenawan Mohamad's definition that works that can be categorized as "religious literature" are works that "place religious life as a solution to problems", it appears that Muhidin and Syaifullah's novels cannot be called "religious literature" in the conventional sense. In this case, as a religiosity rebellion - where religiosity is defined as a philosophy of life or awareness of 'His breath' in everyday life, that is an awareness that is entirely personal and because it is personal, everyone has the right to sue, question, reject or deconstruct his own religious teachings.